Construction of Salmonella Enteritidis and Salmonella Typhimurium ghosts isolated from retail chicken meat - Thung, Tze Young; Chin, Yih Zhet; Mohd Shahril, Najwa; Anyi, Ubong; New, Chia Yeung; Bahumaish, Ramzi Othman Saeed; Kuan, Chee Hao; Mahyudin, Nor Ainy; Basri, Dayang Fredalina; Wan Mohamed Radzi, Che Wan Jasimah; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Salmonellosis is an important public health problem and causes large economic losses in the poultry industry. The emergence of molecular technology has opened various possibilities for constructing tailor-made proteins, particularly protein E from bacteriophage PhiX174 for the production of bacterial ghosts (BGs) applied in vaccines purposes. In the present study, the plamdaPRcI-Elysis plasmid carrying the PhiX174 lysis gene E and thermo-sensitive lamda PR-cl857 regulatory system was constructed. Two Salmonella Enteritidis (SE-2 and SE-4) and one Salmonella Typhimurium (ST-4) isolates were able to uptake the lysis plasmid via electrotransformation. Generation of ghosts was enhanced by increasing the incubation temperature up to 42 ̊C. Cell viability of SE-2, SE-4 and ST-4 decreased ranging in log 2.7 to log 4.1 cycles after lysis induction. Moreover, SE-2 and SE-4 exhibited the earliest reduction of CFU after 3 h of incubation. Our results may provide a promising avenue for the development of Salmonella BGs vaccines.